Prevention of crimes of a terrorist nature by internal Affairs officers - Nikishkin A. V., Stepanov I. V., Nerus D. V. (Relevant issues of management, economics and economic security, 2019)
The authors comprehensively consider the work of the police units involved in the fight against terrorist crimes. The tasks facing such units and activities carried out to reduce the terrorist threat in the country are analyzed
Keywords: безопасность; security; терроризм; terrorism; правоохранительный орган; преступления террористической направленности; террористический акт; общественное место; антитеррористическая деятельность; law enforcement agency; terrorist crimes; terrorist act; public place; antiterrorist activity